2020
DOI: 10.1017/s1049023x20001077
|View full text |Cite
|
Sign up to set email alerts
|

Still Burning: An Exploration of the Impacts of the 2018/2019 Tasmanian Summer Bushfires on Community Pharmacy Operations in Affected Communities

Abstract: Introduction: Human-induced climate change is increasing the likelihood and severity of wildfires across the globe. This has negative consequences for the health of affected communities through the loss of health systems’ infrastructure and disrupted health services. Community pharmacies are a central hub between patients and the health care system and can provide continuity of care during wildfires. However, there is little in peer-reviewed literature about the impacts of wildfires on community pharmacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…33 However, pharmacists are frequently overlooked and struggle to identify who to contact during a pandemic or a local disaster to contribute to health-related disaster decisionmaking processes. 34,35 This continual challenge was evident in our findings, with 76.3% of frontline pharmacists stating they are not engaged with the local disaster and public health groups. This indicates the need for better integration of pharmacists into disaster health teams and for the disaster health community to acknowledge the vital roles and services being undertaken by those essential primary care providers.…”
Section: Discussionmentioning
confidence: 74%
“…33 However, pharmacists are frequently overlooked and struggle to identify who to contact during a pandemic or a local disaster to contribute to health-related disaster decisionmaking processes. 34,35 This continual challenge was evident in our findings, with 76.3% of frontline pharmacists stating they are not engaged with the local disaster and public health groups. This indicates the need for better integration of pharmacists into disaster health teams and for the disaster health community to acknowledge the vital roles and services being undertaken by those essential primary care providers.…”
Section: Discussionmentioning
confidence: 74%
“…However, only nine studies 26,28,35,37,44,64,65,69,70 in this theme discussed a training programme that had been implemented, highlighting that existing climate training and education for the health workforce is limited. Under planning for staff surge capacity, 4,5,8,10,14,27,28,30,31,[33][34][35][36]38,39,[41][42][43][44][45][46][47][48][49][50][53][54][55][56][57][59][60][61][62]67,70,72,[74][75][76] discussions centred on rostering considerations and contingency plans to ensure workforce surge capacity, as well...…”
Section: Responses and Preparationsmentioning
confidence: 99%
“…Under planning for staff surge capacity, 4,5,8,10,14,27,28,30,31,[33][34][35][36]38,39,[41][42][43][44][45][46][47][48][49][50][53][54][55][56][57][59][60][61][62]67,70,72,[74][75][76] discussions centred on rostering considerations and contingency plans to ensure workforce surge capacity, as well as swift and effective mobilisation strategies to quickly increase workforce capacity. Thirty studies reported on the importance of interdisciplinary collaboration, 5,[27][28][29][30][31]33,[36][37]…”
Section: Responses and Preparationsmentioning
confidence: 99%
See 2 more Smart Citations